2014
DOI: 10.1371/journal.pone.0099818
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Phenserine Attenuates Soman-Induced Neuropathology

Abstract: Organophosphorus (OP) nerve agents are deadly chemical weapons that pose an alarming threat to military and civilian populations. The irreversible inhibition of the critical cholinergic degradative enzyme acetylcholinesterase (AChE) by OP nerve agents leads to cholinergic crisis. Resulting excessive synaptic acetylcholine levels leads to status epilepticus that, in turn, results in brain damage. Current countermeasures are only modestly effective in protecting against OP-induced brain damage, supporting intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 85 publications
1
16
0
Order By: Relevance
“…All surgeries and injections were standardized to avoid any additional variables. Sterile heparin-saline was injected using a standardized schedule to prevent clot formation within the catheter (Chen et al 2014;Pan et al 2012a, b).…”
Section: Placement Of External Jugular Vein Catheter (Jvc)mentioning
confidence: 99%
“…All surgeries and injections were standardized to avoid any additional variables. Sterile heparin-saline was injected using a standardized schedule to prevent clot formation within the catheter (Chen et al 2014;Pan et al 2012a, b).…”
Section: Placement Of External Jugular Vein Catheter (Jvc)mentioning
confidence: 99%
“…It proved well tolerated in human studies (645 subjects for up to 1 year) and demonstrated a signal of efficacy in AD . Notably, recent studies have demonstrated a far more interesting pharmacological action, in that it inhibits programmed neuronal cell death (PNCD, eg, apoptosis/autophagy) across multiple cellular and animal neuronal injury models at clinically translatable doses . Detailed within our results described below, across preclinical neuronal injury models particularly in mTBI and modTBI, PhenT mitigates impairments in synaptic integrity, neuroinflammation and inhibits gene pathways leading to AD .…”
Section: Introductionmentioning
confidence: 56%
“…This was appraised by multiple complimentary techniques, including quantitative TUNEL, NeuN, and FJC staining, as well as Western blot quantification of pro‐apoptotic (activated caspase 3) and antiapoptotic (Bcl‐2 and BDNF) protein levels. In addition to these reviewed studies, PhenT has presented PNCD inhibiting actions in rodents challenged with toxic doses of soman, reducing its lethality and, importantly, protecting the brain from neuronal loss . In evaluating mechanisms in the soman study, PhenT was found to regulate a core set of neuroprotective genes termed 'activity‐regulated inhibitor of death' (AID) genes, as well as genes impacting neuroinflammatory pathways.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that soman and other centrallyacting AChE inhibitors via cholinoceptor hyperstimulation start a vicious circle that ends up with glutamatergic excitatory discharges that clinically manifest themselves as seizures and leave the survivors with serious brain damage (45,46). It is not clear what the relation between the onset of seizures and the occurrence of respiratory depression is in soman-poisoned animals, since most of the cited experiments have been performed under urethane anaesthesia (47).…”
Section: Therapeutic Regimens For Anticholin Esteraseinduced Respirmentioning
confidence: 99%